Hubungan Antara Penggunaan Kosmetik Terhadap Terjadinya Akne Vulgaris di Poliklinik Kulit Kelamin Royal Prima dan Murni Teguh Memorial Hospital Kota Medan - Joice Sonya Panjaitan (Universitas HKBP Nommensen, 2020)
Background: Acne vulgaris is the eighth most common disease in the world, with a 9.4% prevalence. Some studies reported that cosmetics’ use could cause and aggravate acne vulgaris. This study was aimed to explore the relation between use of cosmetics on the severity of acne vulgaris. Methods: This was a cross-sectional study from 94 patients in the Dermato-Venereology Clinic in Royal Prima Hospital and Murni Teguh Memorial Hospital Medan in 2019. Subjects were selected by accidental sampling method. The data evaluated in this study were the severity of acne vulgaris measured by the Global Acne Grading System (GAGS) and the level of cosmetic use indicated by Cumulative Cosmetic Exposure Index (CCEI). The relation between variables were analyzed using chi-square. Results: There was no difference between the rates of use of cosmetics on the severity of acne vulgaris (p-value = 0.532). Conclusion: Quantitative use of cosmetics does not affect the severity of acne vulgaris.